PENERAPAN DAN PENILAIAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM ISLAM (ISLAMIC SOCIAL REPORTING) - Anggi Pratiwi Sitorus (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2022)
This article discusses Islamic Social Reporting (ISR) as a new concept of Corporate Social Responsibility with sharia principles. ISR is based on the sharia framework, which is characterized by a relationship between the interests of the world and the hereafter. In its implementation, ISR emphasizes social justice in addition to the environment, minority interests, and jobs. Reporting on company performance in the ISR concept consists of five themes, including financing and investment, products and services, employees, society and the environment.